2022
DOI: 10.2147/ppa.s362464
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Patterns of Self-Reported Nonadherence Using Network Analysis in a Mixed German Cohort

Abstract: Purpose Nonadherence is a complex behaviour that contributes to poor health outcomes; therefore, it is necessary to understand its underlying structure. Network analysis is a novel approach to explore the relationship between multiple variables. Patients and Methods Patients from four different studies (N = 1.746) using the self-reported Stendal Adherence to Medication Score (SAMS) were pooled. Network analysis using EBICglasso followed by confirmatory factor analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…A principal component analysis (PCA) with varimax rotation was performed to assess the underlying structure of the adherence (SAMS) data and to confirm the three factors found in previous literature [12,13,25].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A principal component analysis (PCA) with varimax rotation was performed to assess the underlying structure of the adherence (SAMS) data and to confirm the three factors found in previous literature [12,13,25].…”
Section: Discussionmentioning
confidence: 81%
“…This study revealed several predictors of global nonadherence and different types of nonadherence, which can broadly be divided into patient factors, interpersonal factors, and medication factors [6]. As in our previous work, we used the SAMS to detect modification, missing knowledge, and forgetting to take medication [13,14,25]. These factors were influenced differently by clinical and demographic variables.…”
Section: Discussionmentioning
confidence: 88%
“…One if its advantages is that different facets of adherence are included, namely modification of medication, lack of knowledge and forgetting to take medication 18 22. The SAMS has previously been validated in neurological patients, patients with chronic pain and patients with kidney transplants, and has been used in a variety of studies since 18 23–27…”
Section: Methodsmentioning
confidence: 99%